2005
DOI: 10.1111/j.1365-2745.2005.01044.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Dual role for an allelochemical: (±)‐catechin from Centaurea maculosa root exudates regulates conspecific seedling establishment

Abstract: Summary1 Plant allelopathic compounds may have other roles than interspecific interference. We investigated whether (±)-catechin, a phytotoxin exuded from the roots of the exotic invader Centaurea maculosa (spotted knapweed), is also one of the factors that regulates C. maculosa recruitment. 2 Adding activated carbon, which adsorbs organic compounds, to soil around C. maculosa adults in the field increased seedling density by 78% 25 days after sowing, and by 34% 32 days after sowing, suggesting that soil-borne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 51 publications
4
102
1
1
Order By: Relevance
“…Such an explanation probably does not apply in our case, because applications of mineral solution did not have promoting effects. Alternatively, we suggest that AC may neutralize an autotoxic factor(s) released in the root exudates (Webb et al, 1967;Singh et al, 1999;Perry et al, 2005), or may act as a cue for germination and seedling growth, as reported for charred wood and smoke (Keeley & Fotheringham, 1998). Further, although indirect, support for the phytotoxic hypothesis derives from the response of seedling shoot : root ratios to litter addition.…”
Section: Researchsupporting
confidence: 50%
“…Such an explanation probably does not apply in our case, because applications of mineral solution did not have promoting effects. Alternatively, we suggest that AC may neutralize an autotoxic factor(s) released in the root exudates (Webb et al, 1967;Singh et al, 1999;Perry et al, 2005), or may act as a cue for germination and seedling growth, as reported for charred wood and smoke (Keeley & Fotheringham, 1998). Further, although indirect, support for the phytotoxic hypothesis derives from the response of seedling shoot : root ratios to litter addition.…”
Section: Researchsupporting
confidence: 50%
“…Likewise, the ANR protein from grape also produced (+)-E (Gargouri et al, 2009, and the two CsANRs exhibit higher amino acid sequence identity to VvANR (79% and 83%) than to MtANR or AtANR (64%-73%). In contrast to the widely distributed and well-documented (+)-catechin and (2)-E isomers, there are only a few reports of the presence of (2)-catechin and (+)-E in plants, such as (2)-catechin from Chamaebatia foliolosa and Centaurea maculosa (Nahrstedt et al, 1987;Bais et al, 2003;Perry et al, 2005) and (+)-E from Palmae spp. and Paullinia cupana (Delle Monache et al, 1972;Yamaguti-Sasaki et al, 2007).…”
Section: Tea Anrs and Pa Engineering In Transgenic Plantsmentioning
confidence: 99%
“…Autotoxicity has been widely observed in agricultural crops and weeds, as well as in some plants that inhabit natural systems. Phytotoxic root exudates appear to mediate autoinhibition in at least some of these species, including Asparagus officinalis (garden asparagus), Cucumis sativa (garden cucumber) (Yu et al, 2003) and Centaurea maculosa (spotted knapweed) (Perry et al, 2005).…”
Section: Root-root Communicationmentioning
confidence: 99%